Effects of Acidic Beverages on Color Stability of Bulk-Fill Composites with Different Viscosities - Şişmanoğlu, Soner; Sengez, Görkem (Odovtos - International Journal of Dental Sciences, 2021)
The aim of this in vitro study is to investigate the effects of acidic beverages on the discoloration of bulk-fill composites with different viscosities. 144 disc-shaped specimens (8mm diameter × 2mm thick) were prepared from four different composite resins including a nanohybrid (Filtek Ultimate), two packable bulk-fill (Filtek Bulk Fill, Tetric N Ceram Bulk Fill), and a flowable bulk-fill composite (Tetric N Flow Bulk Fill). The specimens of each group were divided into 3 subgroups and submerged in distilled water, orange juice and coke (n=12). Color difference (∆E) were measured using CIELab color space and a compact spectrophotometer (VITA Easyshade) at baseline and after 30 days of immersion. Data were analyzed using two-way ANOVA and Tukey's HSD post-hoc tests (P<0.05). Two-way ANOVA revealed that both material type and staining solution significantly influenced ∆E values (P<0.001). Immersion in orange juice resulted in greater and significant discoloration over time in comparison to distilled water and coke (P<0.05). Tetric N Ceram (∆E=7.0) and Tetric N Flow (∆E=7.7) bulk-fill restoratives showed highest color change values after 30 days of immersion in orange juice. This study suggests that a discoloration above the clinically acceptable threshold (∆E>2.7) was observed for all bulk-fill composites tested. It can be speculated that orange juice has a more negative effect on the color stability compared to coke. Additionally, flowable bulk-fill composite was more prone to discoloration than condensable bulk-fill composites.